Sequelae of Fat Grafting Postmastectomy: An Algorithm for Management of Fat Necrosis - Doren, Erin L. (Open Science Company, LLC, 2012)
Objective: Fat grafting is used to improve the reconstructed breast. Local recurrences following mastectomy present as palpable subcutaneous nodules; fat necrosis/oil cysts, a sequelae of fat grafting, also present as subcutaneous nodules. Our objective was to examine the frequency and factors associated with fat necrosis in the postmastectomy reconstructed breast and propose an algorithm for management. Methods: A retrospective review of a breast reconstruction database was conducted to identify patients treated with fat grafting. Clinical-pathologic data at cancer presentation, volume of fat injection, occurrence of subcutaneous nodules, and outcome were collected. Statistical analysis was performed to compare the development of a palpable mass with continuous and categorical variables. Results: A total of 278 patients who had fat grafting with breast reconstruction were identified. Sixty-four patients (23%) developed a palpable mass at a median time of 10 months (range: 2-39). Seventeen (6%) subsequently underwent needle or excisional biopsy (16 fat necrosis/oil cysts; 1 recurrent carcinoma). The recurrent carcinoma identified did not correlate with the location of fat grafting. No clinical-pathologic (age, body mass index, stage, smoking, radiation) or technical variables (fat/tumescent volume) were found to predict development of fat necrosis. Conclusions: Fat grafting improves cosmesis but has a significant risk of fat necrosis. Awareness of fat injection location, incidence, time to development, and characteristic examination may decrease anxiety and need for imaging/biopsy.